2022
DOI: 10.3390/molecules27051500
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Various Density Functional Theory Methods for Finding Accurate Structures of Actinide Complexes

Abstract: Density functional theory (DFT) is a widely used computational method for predicting the physical and chemical properties of metals and organometals. As the number of electrons and orbitals in an atom increases, DFT calculations for actinide complexes become more demanding due to increased complexity. Moreover, reasonable levels of theory for calculating the structures of actinide complexes are not extensively studied. In this study, 38 calculations, based on various combinations, were performed on molecules c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…All of the DFT calculations for reference data were done using the ADF software package (2017 release). The PBE exchange-correlation functional with ZORA relativistic effect was employed for each calculation with the large-core triple-ζ basis . Studies have shown that the PBE functional can produce reliable optimized structures and energies for actinide compounds. The scalar relativistic correction is added because it can reach the order 1–2 eV for the 5f shells. , The combination of the computational method has been thoroughly tested in our previous work on the ThO 2 system …”
Section: Dftb Parameterization For the Th–o Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the DFT calculations for reference data were done using the ADF software package (2017 release). The PBE exchange-correlation functional with ZORA relativistic effect was employed for each calculation with the large-core triple-ζ basis . Studies have shown that the PBE functional can produce reliable optimized structures and energies for actinide compounds. The scalar relativistic correction is added because it can reach the order 1–2 eV for the 5f shells. , The combination of the computational method has been thoroughly tested in our previous work on the ThO 2 system …”
Section: Dftb Parameterization For the Th–o Systemmentioning
confidence: 99%
“… 67 Studies have shown that the PBE functional can produce reliable optimized structures and energies for actinide compounds. 68 70 The scalar relativistic correction is added because it can reach the order 1–2 eV for the 5f shells. 71 , 72 The combination of the computational method has been thoroughly tested in our previous work on the ThO 2 system.…”
Section: Dftb Parameterization For the Th–o Systemmentioning
confidence: 99%